2021
DOI: 10.21037/jtd-20-3577
|View full text |Cite
|
Sign up to set email alerts
|

Left heart function evaluation of patients with essential hypertension and paroxysmal atrial fibrillation by two-dimensional speckle tracking imaging combined with real-time three-dimensional ultrasound imaging

Abstract: Background: This study aims to assess the value of two-dimensional speckle tracking imaging (2D-STI) combined with real-time 3-dimensional echocardiography (RT-3DE) in evaluating left heart function in patients with combined ETH and PAF. Methods: A prospective study was designed, and the research period was from January 2017 to January 2020. A PAF observation group comprised of patients with ETH and PAF, a PAF control group of patients with ETH but without PAF, and a healthy volunteer group referred to as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…LAVI max>34 mL/m2 is regarded by the European Society of Cardiology (ESC) as a sign of increased LA [53]. The parameters obtained by calculating the volume changes can also reflect the left atrial function, mainly including the left atrial enlargement index (LAEI), which reflects the storage function, and the Left Atrial Active Ejection Fraction (LAAEF) and Total Ejection Fraction (LATEF) reflecting the auxiliary pump function, the Left Atrial Passive Ejection Fraction (LAPEF), which reflects conduit function, and the Left Atrial Function Index (LAFI), which reflects the overall function of the left atrium [54]. Jiang et al combined 2D-STI with RT3DE to evaluate atrial remodeling and functional changes in patients with AF accompanied by essential hypertension.…”
Section: Imaging Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…LAVI max>34 mL/m2 is regarded by the European Society of Cardiology (ESC) as a sign of increased LA [53]. The parameters obtained by calculating the volume changes can also reflect the left atrial function, mainly including the left atrial enlargement index (LAEI), which reflects the storage function, and the Left Atrial Active Ejection Fraction (LAAEF) and Total Ejection Fraction (LATEF) reflecting the auxiliary pump function, the Left Atrial Passive Ejection Fraction (LAPEF), which reflects conduit function, and the Left Atrial Function Index (LAFI), which reflects the overall function of the left atrium [54]. Jiang et al combined 2D-STI with RT3DE to evaluate atrial remodeling and functional changes in patients with AF accompanied by essential hypertension.…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…Jiang et al combined 2D-STI with RT3DE to evaluate atrial remodeling and functional changes in patients with AF accompanied by essential hypertension. They found that LAVI, LAEI, and LATEF improved significantly with treatment [54]. Zhang et al used the RT3DE method to evaluate left atrial end-diastolic volume index (ILAEDV), End-Systolic Volume Index (ILAESV), and Left Atrial Ejection Fraction (LAEF) in 50 pairs of AF patients and healthy individuals, then compared it with Two-Dimensional Echocardiography (2DE).…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…At present, our study only explored the changes of left atrial-ventricular volume by LA-LV V-LOOP in healthy adults. Previous studies have shown that the volume of left atrium and ventricle also has great diagnostic and predictive value for other heart diseases, such as hypertensive heart disease [24], sepsis cardiomyopathy [25], dilated cardiomyopathy[26], heart failure [27] and so on. Next, we plan to explore other heart diseases accordingly.…”
Section: Further Studymentioning
confidence: 99%
“…Real-time 3D echocardiography (RT-3DE) and speckle tracking imaging (STI) are new modalities that have recently been introduced into clinical practice (8). RT-3DE does not assume the chamber geometry, can visually display the cardiac space structure and ventricular wall motion, and can provide direct measurement of the cardiac capacity and function (9,10). STI can be used to quantify all aspects of myocardial strain related to myocardial deformation and contractile function by measuring the displacement between 2 different points in a myocardial segment (11).…”
Section: Introductionmentioning
confidence: 99%